2021
DOI: 10.1111/jfb.14922
|View full text |Cite
|
Sign up to set email alerts
|

Conservation implications of revised genetic structure resulting from new population discovery: the threatened eastern sand darter (Ammocrypta pellucida) in Canada

Abstract: Human activity can put non-game fishes at higher risk of extinction because of inappropriate management action. Eastern sand darter (Ammocrypta pellucida), a small benthic fish classified as threatened across much of its northern range, inhabits increasingly fragmented sandy habitats and, as a non-game fish, may be easily over-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Similar patterns were identified in Eastern Sand Darter Ammocrypta pellucida, another endangered freshwater species in the provinces of Ontario and Quebec and the states of New York, Michigan, Pennsylvania, and Vermont, that colonized the Laurentian Great Lakes around the same time as Silver Chub (Mandrak and Crossman 1992). Walter and colleagues found that an Eastern Sand Darter population in West Lake (Ontario) was genetically divergent from those of other populations but similar to Wabash River populations (Walter et al 2022), suggesting a possible shared dispersal route with Silver Chub.…”
Section: Lake Erie Population Is Genetically Divergentmentioning
confidence: 63%
See 1 more Smart Citation
“…Similar patterns were identified in Eastern Sand Darter Ammocrypta pellucida, another endangered freshwater species in the provinces of Ontario and Quebec and the states of New York, Michigan, Pennsylvania, and Vermont, that colonized the Laurentian Great Lakes around the same time as Silver Chub (Mandrak and Crossman 1992). Walter and colleagues found that an Eastern Sand Darter population in West Lake (Ontario) was genetically divergent from those of other populations but similar to Wabash River populations (Walter et al 2022), suggesting a possible shared dispersal route with Silver Chub.…”
Section: Lake Erie Population Is Genetically Divergentmentioning
confidence: 63%
“…Walter and colleagues found that an Eastern Sand Darter population in West Lake (Ontario) was genetically divergent from those of other populations but similar to Wabash River populations (Walter et al. 2022), suggesting a possible shared dispersal route with Silver Chub.…”
Section: Discussionmentioning
confidence: 98%
“…Although Atlantic salmon represent an extraordinary example where extensive amounts of genetic and genomic data that can inform conservation units are available, we expect that such large datasets will become increasingly common over the next decade for many species, as genomic resources become more widely accessible (Blanchet et al, 2017 ; Leigh et al, 2021 ). Already genetic datasets have been used to inform genetic discreteness or isolation of conservation units in recent decades (COSEWIC, 2010b ; Mee et al, 2015 ; Walter et al, 2022 ). However, genomic datasets are only starting to be used to inform on the question of evolutionary significance (COSEWIC, 2010a ; Forester et al, 2022 ; Waples et al, 2022 ; Xuereb et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Microsatellites can be used to reveal inbreeding, hybridization, and genetic structure (Honka et al 2022). Furthermore, the microsatellite is often used in animal conservation to see the impact of conservation on genetic factors (Walter et al 2021). Furthermore, microsatellites are extremely useful with low-quality samples, become inexpensive, and take time to develop (Castoe et al 2012).…”
Section: Introductionmentioning
confidence: 99%